Clinical utility of smartphone-based digital infrared thermal imaging in predicting vascular compromise in free flaps - Padmalakshmi Bharathi Mohan; S. Dineshkumar; Devi Prasad Mohapatra; Prasanth Penumadu; M.T. Friji; Ravi Kumar Chittoria (Journal of Current Research in Scientific Medicine)
Background: Flap monitoring plays an important role in avoiding morbidity in free flap. Clinical monitoring is considered the gold standard, but it is subjective. Digital thermal imaging captures and displays the infrared radiation emitted from an object. This is useful in assessing temperature difference between two surfaces, as well as variation of temperature. Smartphone thermal imaging can be used to assess the tissue perfusion, which requires little training. Materials and Methods: The aim was to assess the validity of Digital Thermal Imaging in early diagnosis of flap failure, compared to conventional clinical methods. Eleven patients of microvascular-free flap reconstruction for defects following malignancy and trauma were included in the study for January 25, 2019–March 25, 2021. Flaps were monitored using three different methods – clinical monitoring, biochemical monitoring, and digital thermal imaging done at the following interval: (1) intraoperative (end of surgery), (2) hourly – for the first 48 h, (3) every 4th hourly on postoperative days 3–5, and (4) every 6th hourly on postoperative days 5–10, and the results were tabulated. Results: Flap temperature was observed to be higher compared to the surrounding skin when there was an event of venous thrombosis. The surrounding skin temperature was to be measured on the side opposite to the side where the flap was raised to do vascular anastomosis. The increase in the temperature difference almost coincided with the clinical and biochemical indicator of failing flaps. Conclusion: Monitoring of the flap temperature and comparing it with the surrounding skin temperature can be incorporated along with the gold standard. It is a simple, objective, and noncontact method compared to clinical monitoring and biochemical methods. A large sample size, multicentric, randomized controlled study is required to validate the same.